Length-weight relationship and population dynamics study of the giant catfish (Arius thalassinus) in the Bay of Bengal coast of Bangladesh (Research in Agriculture Livestock and Fisheries, 2020)
The present study investigated the length-weight relationship, population parameters and the instantaneous natural mortality rate of Arius thalassinus from two major landing center of Bangladesh using the FAO-ICLARM Stock Assessment Tools (FiSAT II). A total of 1789 specimens were collected between January 2016 and December 2017. The estimated values of the exponent “b” was ranged from 3.019 (pre-monsoon) to 3.293 (monsoon), indicating an isometric growth pattern of the species with high correlation coefficients (0.904 to 0.927). The equation of length–weight relationship was: W=0.005L3.181. Model parameters of the von Bertalanffy growth equation were: L∞ = 97.60 cm and K = 0.33-1 year. The estimated growth performance index (Ø) was 3.497. The instantaneous natural mortality rate (M) was 0.62-1 year and a high exploitation rate (E) 0.62 (>0.50) showed that this fish is over-exploited in the Bay of Bengal coast of Bangladesh.Res. Agric., Livest. Fish.6(3): 439-444, December 2019